2008
DOI: 10.1016/j.ejvs.2008.08.013
|View full text |Cite
|
Sign up to set email alerts
|

The Pink Pulseless Hand: A Review of the Literature Regarding Management of Vascular Complications of Supracondylar Humeral Fractures in Children

Abstract: Supracondylar fractures of the humerus are the commonest upper limb fractures in children, accounting for up to 70% of all paediatric elbow fractures [Wilson MJ, Hunter JB. Supracondylar fractures of the humerus in children--wire removal in the outpatient setting. Injury Extra 2006 Aug;37(8):313-315] and are often complicated by neurovascular injury. Much confusion surrounds the management of the child with a "pink pulseless hand" post-fracture reduction and several treatment options have been proposed includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 16 publications
0
37
0
6
Order By: Relevance
“…Experience has shown that many children with vascular compromise following trauma can be treated expectantly. As a result, some authors suggest an initial conservative approach to the management of blunt vascular trauma in children first [9,11,12]. Others advocate a more active, management, pointing to possible long term sequelae such as claudication etc [7,10,13].…”
Section: Discussionmentioning
confidence: 98%
“…Experience has shown that many children with vascular compromise following trauma can be treated expectantly. As a result, some authors suggest an initial conservative approach to the management of blunt vascular trauma in children first [9,11,12]. Others advocate a more active, management, pointing to possible long term sequelae such as claudication etc [7,10,13].…”
Section: Discussionmentioning
confidence: 98%
“…4 However, opinions differ about the management of those who do not recover a radial pulse but have good peripheral perfusion as judged by a pink and warm hand. 1,3,12,19,20 Whereas Choi et al 18 considered that reduction of the fracture alone is usually sufficient, White et al 12 considered that absence of the pulse indicates arterial injury even if the hand appears pink and warm, and recommended further vascular investigations in such cases.…”
Section: Discussionmentioning
confidence: 99%
“…This is a slightly higher incidence than the 2.6% to 20% hitherto reported for a pulseless hand with this fracture. [1][2][3][4] There is general agreement that the initial treatment for a patient with a displaced supracondylar fracture with a pulseless but well-perfused hand is prompt closed reduction under general anaesthesia and percutaneous K-wire fixation. 18 This treatment allows recovery of the radial pulse in about 55% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have strongly advocated for routine brachial artery exploration, 2,3,7-9 while others have suggested that affected children can be safely observed if Doppler signals are present in the wrist arteries. 6,[10][11][12][13] Nonoperative management is predicated on the assumption that PPH results from local arterial spasm, but the mechanism of arterial compromise has not been investigated. Reliance on collateral flow in the forearm may leave the hand viable, but puts the child at risk for long-term sequelae such as contractures and limblength discrepancy.…”
mentioning
confidence: 99%